Bridget Jones's diary a novel - Fielding, Helen 1958- (Picador, 1997)
Bridget Jones takes readers on a tour of a hilarious year-in-the-life of a confused thirty-something singleton who would have all the answers if she could just lose seven pounds, stop smoking, and attain inner poise.
Keywords: Single women -- England -- London -- Fiction; Fiktionale Darstellung